The Relationship Between Public Debt And Selected Economic Indicators Of Iraqi Economy: An Analytical Study (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
In recent years, the increasing frequency of credit financing activities in Iraq's public and household sectors has led to the rapid expansion of public and household debt. There are some common determinants of changes in people and household debt. The article uses statistical data from 2004 to 2020 to examine common determinants of public and household debt changes. The study found that the continuous increase in the size of Iraq's public debt and internal debt resulting from a combination of factors such as oil exports, savings, gross domestic product, interest rates on loans, housing prices. We find compelling evidence for a negative relationship between debt and development. Furthermore, there is no linear relationship between expansion and expansion for some of these economic factors. The government and related departments should start with reasonable control, adjust taxes, establish a sound social system to prevent the risks of high public debt and debt, and maintain macroeconomic stability.